Intra-arterial vasodilators infusion for management of reversible cerebral vasoconstriction syndrome in a 12-year-old girl: A case report - Rizzati, Frida; Marie, Guillaume; Chanez, Vivianne; Ferry, Thomas; Natterer, Julia; Longchamp, David; Saliou, Guillaume; Perez, Maria-Helena (Frontiers in Pediatrics, 2023)
Reversible cerebral vasoconstriction syndrome (RCVS) is a vascular disease characterized by diffuse transient vasoconstriction and vasodilatation of the cerebral arteries. It is commonly associated with recurrent severe acute headaches with or without focal neurological deficits, due to haemorrhages, infarcts, and even posterior reversible encephalopathy syndrome (PRES). The optimal management of acute neurologic deficits caused by RCVS is still uncertain. Calcium channel blockers (CCB) such as nimodipine or verapamil have been reported to be effective in adult series. Intra-arterially injection of nimodipine, verapamil and milrinone has recently been demonstrated to be safe and effective for the treatment of severe segmental vasoconstriction in adults. CCB are the most used treatment in the available paediatric literature. Intra-arterial vasodilators have been reported in some rare paediatric reports with more severe disease, but their utility is still under investigation. We report a case of a 12-year-old girl who underwent a severe course of RCVS complicated by multiples cerebral infarcts, treated by several sessions of intra-arterial vasodilators infusion.